Plasma-to-Red Cell Ratio and Mechanism of Injury in Massively Transfused Combat Casualties. Issue 1 (1st January 2014) - Hardin, Mark O.; Ritchie, John D.; Aden, James K.; Blackbourne, Lorne H.; White, Christopher E.
ABSTRACT: Study design: A retrospective review of 930 combat casualties from March 2003 to September 2009 who received a massive transfusion. Mechanism was categorized as explosion (EXPL) (712), gunshot wound (GSW) (190), and blunt trauma (28). Cohorts were also categorized by fresh frozen plasma (FFP) to red blood cell (RBC) ratio: low, ≤1:1.5 and high, >1:1.5. Patient characteristics and in-hospital mortality rates were compared among groups. Propensity matching was used to control for confounding variables. Results: Cohorts were similar in demographics, admission vital signs, and laboratory values. Median injury severity score was higher in EXPL compared to GSW. High FFP:RBC ratio was associated with improved survival compared to low ratio in the EXPL group ( p < 0.01). The GSW group had similar survival in the high and low FFP:RBC ratio groups ( p = 0.06). After propensity matching, a high FFP:RBC ratio was associated with improved survival compared to low ratio in both the EXPL ( p < 0.01) and GSW groups ( p = 0.05). Conclusions: High FFP:RBC ratios are associated with improved survival in combat casualties regardless of injury mechanism.